2017
DOI: 10.22159/ajpcr.2017.v10i4.16631
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of process parameters for production of antimicrobial metabolites by an endophytic fungus Aspergillus sp. CPR5 isolated from Calotropis procera root.

Abstract: Objective: To study the antimicrobial activity of crude ethyl acetate extract from endophytic fungus in Calotropis procera root.Methods: Endophytic fungus was screened for production of antimicrobial metabolites. Fermentation was carried out in 500 ml Erlenmeyer flask. Disc diffusion method was used to test antimicrobial activity of crude extract using chloramphenicol sulfate and fluconazole as a positive control.Results: A total of 14 endophytic fungi were isolated (CPR1-CPR14). Among these 14 isolates, CPR5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
(18 reference statements)
2
11
0
Order By: Relevance
“…It inhibits the process of mitochondrial protein synthesis [26]. Addition of this antibiotic on chick serum indicates the role of chloramphenicol on chick serum and also validates Beer-Lambert's law (Table 6).…”
Section: Nanda and Suneethasupporting
confidence: 69%
“…It inhibits the process of mitochondrial protein synthesis [26]. Addition of this antibiotic on chick serum indicates the role of chloramphenicol on chick serum and also validates Beer-Lambert's law (Table 6).…”
Section: Nanda and Suneethasupporting
confidence: 69%
“…Anwar and Iqbal (2017) also studied the effect of growth media on antibacterial activity, and suggested that secondary metabolites are highly affected by the composition of the growth medium. Verma et al (2017) found that starch was the source of carbon allowing the endophytic fungus to produce the highest amount of bioactive molecules followed by glucose. This is in agreement with the results obtained with MPR1 on PDA and MEA that contain the appropriate concentration of starch and glucose.…”
Section: Selection Of Suitable Culture Mediamentioning
confidence: 99%
“…It has been reported that each group of plants from thallophytes to spermatophytes and from hydrophytes to xerophytes harbor endophytic microbiota [ [35] , [36] , [37] ]. Endophytes like fungus, bacteria, and actinomycetes have been found as the most useful and greatly diverse group of microbiota to reside within the plants of the different part of the globe, such as rainforests [ 38 ], oceans [ 39 ], mangrove swamps [ 40 ], Arctic [ 41 ], Antarctic [ 42 ], coastal forests [ 43 ], geothermal lands [ 44 ], and deserts [ 45 ].…”
Section: Biodiversity Of Endomicrobiome Of Plantsmentioning
confidence: 99%
“…They also have been isolated from ferns, gymnosperms, and angiosperms of the tropical forests, diverse xeric climates, extreme arctic flora, and boreal forests [ 46 , 47 ]. There are myriad reports indicates that diversified environmental conditions comprising drought [ 32 , 33 ], low temperature [ 48 ], elevated temperature [ [49] , [50] , [51] ], high salinity [ 52 ], and multiple extreme conditions [ [35] , [36] , [37] , 53 ] are responsible for niche-specific diversity of the microbial community. Moreover, the term endophyte is a topographical term that comprises all the organisms that asymptomatically reside within the living internal tissues of the plant parts of the host at any stage of their life.…”
Section: Biodiversity Of Endomicrobiome Of Plantsmentioning
confidence: 99%
See 1 more Smart Citation